The Oxford handbook of creativity, innovation, and entrepreneurship / edited by Christina E. Shalley, Michael A. Hitt, and Jing Zhou. - Shalley, Christina E.; Hitt, Michael A.; Zhou, Jing, 1964 August 25-; Amabile, Teresa.; Tushman, Michael.; Raffaelli, Ryan L.; Shalley, Christina E.; Hitt, Michael A.; Zhou, Jing, 1964 August 25- (Oxford library of psychology., 2015)
Research-based investigations of creativity, innovation, and entrepreneurship have the potential to inform each other and enrich our knowledge of each of these areas, particularly with regard to cognitive processes and effective behaviours. Yet, while these research streams have increasingly received a great deal of attention, they have developed largely independently of one another. This handbook addresses the critical need to integrate these three interrelated literatures.